Phylogeny of Neotropical Castniinae (Lepidoptera: Cossoidea: Castniidae): testing the hypothesis of the mimics as a monophyletic group and implications for the arrangement of the genera. (7th January 2014) - Moraes, Simeão de Souza; Duarte, Marcelo
<x xml:space="preserve">Abstract</x> A cladistic analysis of the Neotropical Castniidae is presented using 120 morphological characters, and a taxonomic treatment based on that analysis is also presented. The tribe Gazerini as previously delimited was found to be paraphyletic with respect to the genera Ceretes, Divana, Riechia, Frostetola, and Oiticicastnia. The genera Castnia, Geyeria, and Athis were also found to be non‐monophyletic taxa. The mimicry pattern had multiple independent origins in the Neotropical castniids, and at least two lineages, Riechia and Prometheus, are involved in Batesian mimicry rings with unpalatable butterfly models in the tribes Acraeini and Heliconiini (Nymphalidae). We propose for Castniini 13 new synonymies and 27 new combinations. Geyeria strigata (Walker, 1854) is revalidated. The generic placements of Athis superba (Strand, 1912) and Castnia eudesmia Gray, 1838 are questionable, but presently upheld. © 2014 The Linnean Society of London